Zooming in on major mergers: dense, starbursting gas in cosmological simulations - Sparre, Martin; Springel, Volker (Arxiv, 2016)
We introduce the `Illustris zoom simulation project', which allows the study of selected galaxies forming in the $Λ$CDM cosmology with a 40 times better mass resolution than in the parent large-scale hydrodynamical Illustris simulation. We here focus on the starburst properties of the gas in four cosmological simulations of major mergers. The galaxies in our high-resolution zoom runs exhibit a bursty mode of star formation with gas consumption timescales 10 times shorter than for the normal star formation mode. The strong bursts are only present in the simulations with the highest resolution, hinting that a too low resolution is the reason why the original Illustris simulation showed a dearth of starburst galaxies. Very pronounced bursts of star formation occur in two out of four major mergers we study. The high star formation rates, the short gas consumption timescales and the morphology of these systems strongly resemble observed nuclear starbursts. This is the first time that a sample of major mergers is studied through self-consistent cosmological hydrodynamical simulations instead of using isolated galaxy models setup on a collision course. We also study the orbits of the colliding galaxies and find that the starbursting gas preferentially appears in head-on mergers with very high collision velocities. Encounters with large impact parameters do typically not lead to the formation of starbursting gas.